Murtad Bukan Penyebab Utama Perceraian? (Analisis Putusan Pengadilan Agama Banjarmasin Nomor: 433/Pdt.G/2021/PA. Bjm) - ardi, sahibul (An-Nahdhah | Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2023)
Marriage is a sacred bond that has an attachment not only to fellow human beings (husband and wife) but is heavier on bonds to God in terms of one's beliefs and faith, this is because there are obligations and rights that bind individuals in a marriage. Related to this, it is very necessary to study the things that form the basis of a marriage, and what problems make a marriage end in a divorce. This research examines one of the reasons for differences in beliefs between husbands and wives, which differences occur after marriage. Then, is apostasy (a person leaving Islam) the main cause of divorce in case Number 433/Pdt.G/2021/PA. BJMs? This is what will be analyzed and studied. As for the decision of the Judge of the Banjarmasin Religious Court regarding this case not to accept the Petitioner's request to be granted permission to impose one raj'i divorce against the Respondent because it was not based on law, then this matter does not conflict with the ratio legis of Article 189 paragraph (3) R.Bg. This is appropriate considering that the pledge of divorce is related to the practice of Islamic law, while the Defendant has actually proven that he has left Islam (apostate) and an apostate is not justified/has no right to pronounce a divorce vow. Therefore, apostasy is not the main cause of divorce in the Religious Courts, because apostasy is what causes husbands to be unable to divorce their wives because Islamic law no longer applies to them.